Enantioselective Difunctionalization of Alkenes by a Palladium‐Catalyzed Heck/Sonogashira Sequence. Issue 7 (27th December 2019) - Zhou, Lujia; Li, Sanliang; Xu, Bing; Ji, Danting; Wu, Lizuo; Liu, Yu; Zhang, Zhan‐Ming; Zhang, Junliang
Abstract: Sonogashira‐type cross‐couplings are one of the most significant alkynylations in organic chemistry. One of the first palladium‐catalyzed intramolecular Heck/Sonogashira reactions of alkenes with terminal alkynes is now reported. With this method, a variety of uniquely substituted chiral benzene‐fused heterocycles bearing a propargyl‐substituted all‐carbon quaternary stereocenter were obtained in a straightforward, high‐yielding, and highly stereoselective manner under mild conditions. Salient features of this process include the use of readily available substrates, high selectivities, a broad substrate scope as well as versatile product functionalizations. Abstract : Dual functionalization : An enantioselective palladium‐catalyzed aryl‐alkynylation of alkenes by a Heck/Sonogashira sequence enables the efficient synthesis of various chiral benzene‐fused heterocycles bearing a propargylic all‐carbon quaternary stereocenter. Salient features of this process include the use of readily available substrates, high selectivities, and a broad substrate scope.